2021
DOI: 10.1038/s41598-021-92778-9
|View full text |Cite
|
Sign up to set email alerts
|

Neu1 deficiency induces abnormal emotional behavior in zebrafish

Abstract: NEU1 sialidase hydrolyzes sialic acids from glycoconjugates in lysosomes. Deficiency of NEU1 causes sialidosis with symptoms including facial dysmorphism, bone dysplasia, and neurodegeneration. However, the effects of NEU1 deficiency on emotional activity have not been explored. Here, we conducted the behavioral analysis using Neu1-knockout zebrafish (Neu1-KO). Neu1-KO zebrafish showed normal swimming similar to wild-type zebrafish (WT), whereas shoaling was decreased and accompanied by greater inter-fish dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Studies in zebrafish reported that NEU1-KO zebrafish developed behavioral traits opposite to ASD, including excessive exploratory/boldness behavior on various tests. Furthermore, anxiety induction upregulated NEU1 expression in zebrafish ( 35 ), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in zebrafish reported that NEU1-KO zebrafish developed behavioral traits opposite to ASD, including excessive exploratory/boldness behavior on various tests. Furthermore, anxiety induction upregulated NEU1 expression in zebrafish ( 35 ), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…It is intriguing that the role of NEU1 in AD may be supported by very recent studies performed on the Neu1-KO zebrafish model. Ikeda et al suggested the link of Neu1 with altered emotional activity, pointing to a deregulated lysosomal exocytosis, probably as suggested 8 years earlier (Annunziata et al, 2013;Ikeda et al, 2021).…”
Section: Neu1's Deficiency-related Lysosomal Exocytosis and Neuropsyc...mentioning
confidence: 91%
“…Importantly, this process has been implicated in pathologies related to the central nervous system, such as neurodegeneration ( d’Azzo et al, 2015 ; Khan and Sergi, 2018 ) and changes in the emotional behavior of an animal model ( Ikeda et al, 2021 ). It is intriguing that the role of NEU1 in AD may be supported by very recent studies performed on the Neu1-KO zebrafish model.…”
Section: Neu1 As a Negative Regulator Of Lysosomal Exocytosismentioning
confidence: 99%
See 2 more Smart Citations